Expression and Clinical Significance of TIGIT in Primary Breast Cancer - Tang L; Sha M; Guo T; Lu H; Qian J; Shao Q; Ye J (International Journal of General Medicine, 2023)
Limin Tang,1 Min Sha,2 Ting Guo,2 Huimin Lu,2 Jingyu Qian,2 Qixiang Shao,1 Jun Ye2 1Department of Immunology, School of Medicine, Jiangsu University, Zhenjiang, Jiangsu, People’s Republic of China; 2Department of Central Laboratory, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, Jiangsu, People’s Republic of ChinaCorrespondence: Jun Ye, Department of Central Laboratory, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, 399 Hailing Road, Taizhou, Jiangsu, 225300, People’s Republic of China, Tel +86-13625171902, Email m13625171902@163.comPurpose: The roles of T cell immunoreceptor with Ig and ITIM domains (TIGIT) in the diagnosis of primary breast cancer (PBC) are still unclear. This study was designed to investigate the expression of TIGIT in PBC patients, with an aim to analyze its diagnostic value in PBC.Patients and Methods: We first explore the expression of TIGIT in cancer patients based on TCGA database, and then we analyzed its correlation with clinicopathological features. Afterwards, we compared the protein and mRNA expressions of TIGIT in two BC cell lines (MCF-7 and MDA-MB-231) and normal breast epithelial cell line (MCF-10A). Subsequently, 56 PBC female patients admitted to the Taizhou People’s Hospital from October 2018 to June 2021 were included in this study. Flow cytometry was used to detect TIGIT level on peripheral blood CD3+ T cells of PBC patients and healthy controls. TIGIT expression in PBC tissues was detected by immunohistochemistry (IHC) and immunofluorescence staining.Results: TCGA database showed that compared with adjacent tissues, TIGIT was significantly upregulated in tumor tissues. High TIGIT expression was positively correlated with tumor stage and negatively correlated with recurrence free survival (RFS) and overall survival (OS). TIGIT level in BC cell lines, peripheral blood and tumor tissues of PBC patients was significantly higher than that of control (P < 0.05). TIGIT level was correlated with age (P < 0.05), rather than tumor size, pathological type, lymph node metastasis, ER, PR, HER-2, and P53. ROC curve showed that the optimal critical value of peripheral blood TIGIT for BC screening was 23.38%. Postoperative TIGIT level in peripheral blood was significantly decreased compared to the preoperative TIGIT level (P < 0.05).Conclusion: TIGIT was upregulated in PBC and was correlated with age. It may be a potential target for the diagnosis and immunotherapy of PBC.Keywords: TIGIT, primary breast cancer, immune checkpoint, tumor immunity, bioinformatics analysis